BACTERIOPHAGES AND THEIR EFFECT ON BACTERIAL BIOFILMS - Є. С. Воробєй; О. С. Воронкова; I. В. Маліновська; А. I. Вінніков (Mìkrobìologìâ ì Bìotehnologìâ. Мікробіологія і біотехнологія, 2013)
The review is devoted to the questions of bacteriophages and bacterial cells interaction in a biofilm and to opportunities of regulation of biofilm growth by bacteriophages. Wide spread of antibioticresistance of clinical isolates of bacteria and decreasing of antibiotic therapy efficacy requires a new solution. In modern clinical practice there were observed increasing of number of the infections caused by bacterial biofilm, besides bacteria, as a part of this structure, possess some advantages, including resistance to antibiotics. The features of phage infection in plankton culture and in biofilm are shown. Submitted data describe possibilities of bacteriophages used against bacterial biofilms, which consist of conditionally-pathogenous bacteria. Data on the mechanism of interaction of phages with cells of bacteria are provided in a biofilm as well as possibility to destruct intercellular matrix by phage encoded enzymes.